(Former Yugoslav) Republic of Macedonia of the Crossroad in Search of Identity(es) - Vinarov, Ivan (Research Papers, 2019)
The current research aims is to rise the current questions about the identity of the Macedonians. Its implementation clarifies the essence of the term "identity" and the process of social engineering in Macedonia. Further content analysis of media information and statistics from indices of international organizations is used. The main conclusion is that a paradoxical process is being developed – a transformation of the past in order to restructure the future in a different way.